China and the EU in the era of regional and interregional cooperation - P.I.E. - Peter Lang S.A. (International issues, 2020)
This book is the outcome of a multi-annual study of Chinese and European research institutions that addresses the partnership between the EU and China and its political and economic implications. The book's distinct focus is to situate this multipurpose relationship within the context of the multidisciplinary academic debate about China's interregional relations with specific regions (i.e. Europe, Southeast Asia, Latin America, Africa, Middle East), notably the Belt and Road initiative (BRI). Both the economic and political dimensions of the international rise of China are critically analysed, with special attention to opportunities, risks, challenges and controversial issues. The international set of authors uniquely combines academics and decision makers as well as experts and think tank leaders.